A Term Infant Presenting with COVID-19 Disease at Birth and a Croup-Like Cough - Arnold, Michelle; Wade, Christine; Micetic, Becky; Mody, Kartik (American Journal of Perinatology, 2022)
Objective Since the global outbreak of the novel coronavirus disease 2019 (COVID-19), there have been increasing reports of children developing a croup-like cough associated with concurrent COVID-19 infection. Currently, there is not much information available regarding newborn infants and COVID-19 infection and the incidence of vertical transmission is thought to be rare. This novel case report depicts a term newborn infected at the time of birth with COVID-19 and includes details about the course of their complicated hospitalization.Study Design A term infant, found to be infected at birth with COVID-19, developed respiratory distress resulting in transfer to our neonatal intensive care unit. Due to the increasing respiratory support requirements, endotracheal intubation was required on day of life (DOL) 7. Later, when the infant was extubated, on DOL 21, a croup-like cough developed. Results Despite respiratory treatment with albuterol, budesonide, racemic epinephrine, lidocaine, dornase alfa, and a 10-day course of dexamethasone, the cough persisted. A prolonged hospitalization was required and eventually the infant was discharged home on 0.4 L/minute of oxygen via nasal cannula on DOL 95.Conclusion As the COVID-19 virus mutates over time, there are some seemingly different presentations in both the pediatric and adult populations. The hypervigilance and sharing of new findings among providers are paramount in the treatment of infants with COVID-19 disease.Key Points
Keywords: newborn; infant; COVID-19; neonatal intensive care unit; croup; cough; respiratory distress